2009
DOI: 10.1186/1465-9921-10-114
|View full text |Cite
|
Sign up to set email alerts
|

Role of lysophosphatidic acid receptor LPA2 in the development of allergic airway inflammation in a murine model of asthma

Abstract: BackgroundLysophosphatidic acid (LPA) plays a critical role in airway inflammation through G protein-coupled LPA receptors (LPA1-3). We have demonstrated that LPA induced cytokine and lipid mediator release in human bronchial epithelial cells. Here we provide evidence for the role of LPA and LPA receptors in Th2-dominant airway inflammation.MethodsWild type, LPA1 heterozygous knockout mice (LPA1+/-), and LPA2 heterozygous knockout mice (LPA2+/-) were sensitized with inactivated Schistosoma mansoni eggs and loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
75
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(78 citation statements)
references
References 54 publications
2
75
1
Order By: Relevance
“…Chemical conversion of lysophospholipid such as LPC to LPA can also occur in the presence of strong acid ( 26 ). The most commonly reported sample preparation method for LPA extraction from biological fl uids involves LLE with acidification ( 3,12,14,15,18,19,(27)(28)(29). Scherer et al showed that under strong acidic conditions, LPC degrades to LPA in the presence of plasma, and the total LPA concentration in human plasma was almost 10-fold higher in plasma extracted under acidic conditions versus plasma extracted polypropylene microcentrifuge tube) was spiked with 10 µl of internal standard (IS) (C17:0-LPA) working solution (in methanol) followed by 200 ul of extraction buffer (30 mM citrate/40 mM sodium phosphate in water) and 600 µl of butanol.…”
Section: Methodsmentioning
confidence: 99%
“…Chemical conversion of lysophospholipid such as LPC to LPA can also occur in the presence of strong acid ( 26 ). The most commonly reported sample preparation method for LPA extraction from biological fl uids involves LLE with acidification ( 3,12,14,15,18,19,(27)(28)(29). Scherer et al showed that under strong acidic conditions, LPC degrades to LPA in the presence of plasma, and the total LPA concentration in human plasma was almost 10-fold higher in plasma extracted under acidic conditions versus plasma extracted polypropylene microcentrifuge tube) was spiked with 10 µl of internal standard (IS) (C17:0-LPA) working solution (in methanol) followed by 200 ul of extraction buffer (30 mM citrate/40 mM sodium phosphate in water) and 600 µl of butanol.…”
Section: Methodsmentioning
confidence: 99%
“…GPCR is the largest class of transmembrane receptors in the human genome involved in regulation of proliferation, differentiation, and immune response through the wide variety of its ligands [124]. One of them is lysophosphatidic acid (LPA), a bioactive phospholipid that is a component of normal plasma and biological fluids, such as saliva and bronchoalveolar fluid [125,126]. LPA is capable of inducing diverse cellular responses by inducing activity of several transcription factors, including NF-κB and AP-1 [127].…”
Section: Carma3-mediated Nf-κb Signaling Pathwaysmentioning
confidence: 99%
“…High concentrations of the lipid have been detected in the bronchoalveolar lavage fluid of preclinical animal models of allergic asthma (4). LPA plays a role in regulating the secretion of pro-and anti-inflammatory mediators by airway epithelial cells and in modulating airway epithelial barrier integrity (5).…”
mentioning
confidence: 99%